2020
DOI: 10.1155/2020/9462903
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Perceptions on Health Warning Labels on Cigarette Packs among Smokers: A Cross-Sectional Study

Abstract: Backgrounds. Tobacco use is the leading preventable cause of premature deaths. Tobacco control remains a top priority, and health warning labels (HWLs) are one of the recommended methods. This study is aimed at examining the awareness and perceptions of HWLs on cigarette packs among smokers. Methods. A cross-sectional study was conducted among 240 smokers who were randomly recruited from three townships in Mandalay in 2018. A face-to-face interview was done using a questionnaire. Multivariate logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Several studies from developed countries such as the USA, Japan, United Kingdom, Canada and Australia have reported that large text and pictorial health warnings are associated with an increased likelihood of quitting as opposed to single text- only warnings, regardless of the age or education of those who smoke 13,16,18,19,21,38,[43][44][45] . Another study showed that while effectiveness of health warnings on cigarette packages varied, pictorial warnings with personal testimonials were the most effective across more than 100 countries 41 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies from developed countries such as the USA, Japan, United Kingdom, Canada and Australia have reported that large text and pictorial health warnings are associated with an increased likelihood of quitting as opposed to single text- only warnings, regardless of the age or education of those who smoke 13,16,18,19,21,38,[43][44][45] . Another study showed that while effectiveness of health warnings on cigarette packages varied, pictorial warnings with personal testimonials were the most effective across more than 100 countries 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Health warning labels on cigarette packages serve as one of the primary means of communicating the harmful effects of cigarette smoking 12,13 . Awareness of the health harms of cigarette smoking has been associated with increased thinking about quitting and quit attempts among people who smoke 13 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations